Influence of Chemical Treatments Sequence on Morphology and Crystallinity of Sorghum Fibers - Ismojo Ismojo; Abdul Aziz Ammar; Ghiska Ramahdita; Anne Zulfia; Mochamad Chalid (Universitas Gadjah Mada, 2018)
Micro-fibrillated cellulose (MFC) derived from natural fibre is continuously gaining interest to produce an environmentally-friendly material, due to economic and ecological reasons. In consequence, sorghum is one of the most-cultivated crops that usually remain the waste as by product of bioethanol production. Indeed, it will be a promising area to utilize sorghum waste to produce MFC for enhancing polymer performance, especially in terms of crystallinity. The objective of this study is to investigate the effect of a sequence of chemical modification was applied to sorghum fibres, i.e. alkalization using 4% sodium hydroxide followed by bleaching using 1.7% sodium chlorite plus acetic acid as a buffer. The treatment was purposed to unbundle the lignocellulose networks into microfibrils cellulose with less amorphous part and lower hydrophilic properties. Evaluation of the chemical treatments effect on internal microstructure, crystallinity index and chemical composition of sorghum fibre was measured via Field-Emission Scanning Electron microscope (FE-SEM), X-ray Diffraction (XRD) and Fourier Transformation Infra-Red (FTIR) Spectroscopy. The experiments show that treatments led to a removal of binding materials, such as amorphous parts hemicellulose and lignin, from the sorghum fibres, resulting MFC of sorghum fibres and enhanced crystallinity index from 41.12 % to 75.73%.